Islam Wasathiyah and Acehnese Dayah Ulama: Negotiating Local Tradition and State Religious Discourse - Anzaikhan, M.; Harahap, Syahrin; Adenan, Adenan (Millati: Journal of Islamic Studies and Humanities, 2026)
This study examines the understanding of Islam Wasathiyah from the perspective of Acehnese dayah ulama and explores its negotiation with the state-promoted discourse of religious moderation. Although religious moderation is widely promoted to encourage inclusive and peaceful Islam, the terminology has encountered resistance among dayah ulama in Aceh. This study aims to analyze how Islam Wasathiyah is interpreted within dayah scholarly traditions and to investigate the negotiation between local Islamic traditions and national religious discourse. Employing a qualitative fieldwork-based approach, the study draws on in-depth interviews, limited observation, and document analysis. The findings reveal that dayah ulama reject the term “religious moderation” due to its perceived ideological and political connotations. Nevertheless, they substantively embrace and practice these core values through the concept of Islam Wasathiyah, which is rooted in the tradition of Ahl al-Sunnah wa al-Jama‘ah. In this context, Islam Wasathiyah functions as a dialectical bridge that mediates between local Islamic authority and national religious discourse. This study highlights the importance of cultural sensitivity, linguistic framing, and local religious authority in articulating moderate Islam within the Indonesian context.